MALDI mass spectrometry imaging unravels organ and amyloid‐type specific peptide signatures in pulmonary and gastrointestinal amyloidosis. Issue 6 (12th June 2021) - Schürmann, Jan; Gottwald, Juliane; Rottenaicher, Georg; Tholey, Andreas; Röcken, Christoph
Abstract: Purpose: Amyloidosis is a disease group caused by pathological aggregation and deposition of peptides in diverse tissue sites. Recently, matrix‐assisted laser desorption/ionization mass spectrometry imaging coupled with ion mobility separation (MALDI‐IMS MSI) was introduced as a novel tool to identify and classify amyloidosis using single sections from formalin‐fixed and paraffin‐embedded cardiac biopsies. Here, we tested the hypothesis that MALDI‐IMS MSI can be applied to lung and gastrointestinal specimens. Experimental Design: Forty six lung and 65 gastrointestinal biopsy and resection specimens with different types of amyloid were subjected to MALDI‐IMS MSI. Ninety three specimens included tissue areas without amyloid as internal negative controls. Nine cases without amyloid served as additional negative controls. Results: Utilizing a peptide filter method and 21 known amyloid specific tryptic peptides we confirmed the applicability of a universal peptide signature with a sensitivity of 100% and a specificity of 100% for the detection of amyloid deposits in the lung and gastrointestinal tract. Additionally, the frequencies of individual m/z‐values of the 21 tryptic marker peptides showed organ‐ and tissue‐type specific differences. Conclusions and Clinical Relevance: MALDI‐IMS MSI adds a valuable analytical approach to diagnose and classify amyloid and the detection frequency of individual tryptic peptides is organ‐/tissue‐type specific.